Implementasi Pemanfaatan Akal Imitasi Dalam Meningkatkan Perilaku Inovatif Guru - Natalia Tri Astuti; Nurul Frijuniarsi (CV. Multi Kreasi Media, 2026)
The purpose of this activity is to improve teachers’ innovative behavior through the use of artificial intelligence, as a learning approach based on the ability to imitate and adapt to create new innovations. This activity was carried out at SD Permata Bangsa, which was delayed by the need for teachers to adapt to the development of educational technology and creative learning approaches in the era of independent learning. The method used is Participatory Action Research with the stages of needs analysis, training, mentoring, and reflection. The results of the activity showed an increase in teachers' ability to develop digital-based teaching media with contextual learning methods. Teachers are not only able to imitate practices well, but also are able to modify them into creative solutions according to the context needed in the classroom. This program is expected to be a sustainable model for teacher professional development based on Artificial Intelligence.